Mycobacterium avium chronic infection differently affects the cytokine profile in the hippocampus from Balb/c, C57BL/6 and CD-1 mice but has no impact in behavior - Susana Cristina Roque de Oliveira (2022)
One of the most remarkable findings in the immunology and neuroscience fields was the discovery of the bidirectional interaction between the immune and the central nervous systems. This interplay is tightly regulated to maintain homeostasis in physiological conditions. Disruption in this interplay has been suggested to be associated with several neuropsychiatric disorders. Most studies addressing the impact of an immune system disruption on behavioral alterations focus on acute pro-inflammatory responses. However, chronic infections are highly prevalent and associated with an altered cytokine milieu that persists over time. Studies addressing the potential impact of mycobacterial infections on depressive-like behavior originated discordant results and the subject need to be further address. To promote our understanding on the effect of chronic infections on the central nervous system, we evaluated the impact of Mycobacterium avium infection. Since the profile of cytokines produce vary depending on the mouse strains, three mouse strains were analyzed (Balb/c, C57BL/6 and CD-1). We used female mice and the model of peripheral chronic infection. Our results show that M. avium peripheral chronic infection induces alterations not just in the peripheral immune system but also in the central nervous system, namely in the hippocampus. Interestingly these cytokine alterations vary between mouse strains. These altered cytokine profiles are not accompanied by hippocampal cell proliferation or neuronal plasticity changes. Accordingly, no differences were observed in locomotor, anxious and depressive-like behavior independently on the mouse strains used. These results show that the infection-induced alterations in the cytokine profile, both in the periphery and the hippocampus, are insufficient to alter behavior and hippocampal plasticity.